MPV17 Mutations Are Associated With a Quiescent Energetic Metabolic Profile - Jacinto, Sandra; Guerreiro, Patrícia; de Oliveira, Rita Machado; Cunha-Oliveira, Teresa; Santos, Maria João; Grazina, Manuela; Rego, Ana Cristina; Outeiro, Tiago F. (Frontiers in Cellular Neuroscience, 2021)
Mutations in the MPV17 gene are associated with hepatocerebral form of mitochondrial depletion syndrome. The mechanisms through which MPV17 mutations cause respiratory chain dysfunction and mtDNA depletion is still unclear. The MPV17 gene encodes an inner membrane mitochondrial protein that was recently described to function as a non-selective channel. Although its exact function is unknown, it is thought to be important in the maintenance of mitochondrial membrane potential (ΔΨm). To obtain more information about the role of MPV17 in human disease, we investigated the effect of MPV17 knockdown and of selected known MPV17 mutations associated with MPV17 disease in vitro. We used different approaches in order to evaluate the cellular consequences of MPV17 deficiency. We found that lower levels of MPV17 were associated with impaired mitochondrial respiration and with a quiescent energetic metabolic profile. All the mutations studied destabilized the protein, resulting in reduced protein levels. We also demonstrated that different mutations caused different cellular abnormalities, including increased ROS production, decreased oxygen consumption, loss of ΔΨm, and mislocalization of MPV17 protein. Our study provides novel insight into the molecular effects of MPV17 mutations and opens novel possibilities for testing therapeutic strategies for a devastating group of disorders.